Investigating the effect of rGO on microstructural and electrical properties of La0.9Sr0.1Ga0.8Mg0.2O3 in intermediate temperature SOFCs. Issue 14 (27th June 2022) - Hanif, Muhammad Bilal; Rauf, Sajid; Qayyum, Sana; Šihor, Marcel; Motola, Martin
Abstract : The effect of rGO on LSGM electrolyte composites for SOFC applications at lower sintering temperatures (∼1300 °C). Abstract : Despite the high demand for green energy sources, the low performance of solid oxide fuel cells (SOFCs) at low temperatures hinders their potential practical application. Ceramic reduced graphene oxide (rGO) composites are promising candidates as solid electrolytes for SOFCs enabling efficient heat transfer and effective ionic charge carrier transport. In the present work, x %rGO + LSGM ( x = 0, 0.25, 1, and 2 wt%) composites were fabricated using the sol–gel method, and a thorough characterization of the materials' properties was conducted including structural and electrical properties for their possible use in SOFC applications. XRD was used to investigate the structural properties of x %rGO + LSGM composite precursors. All the XRD patterns corresponding to the LSGM based precursor peaks showed a single phase structure without any impurities. To identify the signal from rGO in the samples manufactured from composite powders, Raman spectra were obtained at different points by using various wavelengths. The microstructure of 2%rGO + LSGM shows ∼96.1% relative density and a grain size of ∼1.86 μm when annealed at 1300 °C for 5 h in air. The temperature dependencies of grain and ionic conductivities of the rGO + LSGM composite precursors were revealed for the first time. Temperature dependence of the ionic conductivity of 2%rGO + LSGM at 750 °C is about 0.051 S cm −1 whereas the grain conductivity of 1%rGO + LSGM is half of the grain conductivity of 2%rGO + LSGM at 550 °C. The activation energy of 0.25–2% rGO with the addition of sintering aids at T > 400 °C is 0.85 eV, 0.81 eV, and 0.86 eV, respectively, leading to efficient ionic conduction at intermediate temperature.